2007
DOI: 10.1097/wno.0b013e31814b22dc
|View full text |Cite
|
Sign up to set email alerts
|

Terson Syndrome With Bilateral Optic Nerve Sheath Hemorrhage

Abstract: A 53-year-old man presented with an acute headache and mental status changes due to rupture of an anterior choroidal artery aneurysm. A preoperative CT scan demonstrated subarachnoid hemorrhage, bilateral optic nerve sheath hemorrhage, and bilateral intraocular hemorrhage. Ophthalmoscopy and B-scan ocular ultrasound disclosed vitreous hemorrhages, features consistent with Terson syndrome. This is the first CT report of Terson syndrome showing bilateral optic nerve sheath hemorrhage.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

1
2
0

Year Published

2010
2010
2021
2021

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 13 publications
(3 citation statements)
references
References 12 publications
1
2
0
Order By: Relevance
“…Our results have shown that OUS as a bedside, non-invasive tool is of high diagnostic value and provides high accuracy detecting ocular pathologies, confirming previous findings by Blaivas et al and others [14] , [15] , [17] , [18] . This is of special interest to neuro-intensive care and neurological rehabilitation units, as OUS is not routinely performed in SAH patients, where IOH followed by temporary or permanent visual acuity may affect nearly half of all patients [6] .…”
Section: Discussionsupporting
confidence: 92%
“…Our results have shown that OUS as a bedside, non-invasive tool is of high diagnostic value and provides high accuracy detecting ocular pathologies, confirming previous findings by Blaivas et al and others [14] , [15] , [17] , [18] . This is of special interest to neuro-intensive care and neurological rehabilitation units, as OUS is not routinely performed in SAH patients, where IOH followed by temporary or permanent visual acuity may affect nearly half of all patients [6] .…”
Section: Discussionsupporting
confidence: 92%
“…6,16 The heavily T2-weighed MR image in the present case revealed that the subarachnoid hemorrhage had entered the intervaginal subarachnoid space of the optic nerve of both eyes. Noting that the dilatation of the subarachnoid space around the optic nerve was more prominent in the left eye, we determined that more blood had entered the subarachnoid space in the left eye.…”
Section: Discussionmentioning
confidence: 96%
“…Increased intracranial venous pressure generated in the retinal veins causes stasis and rupturing of superficial retinal vessels, leading to the intraocular haemorrhage. This theory explains the occurrence of Terson syndrome in cases other than subarachnoid haemorrhage [2,5,8].…”
Section: Discussionmentioning
confidence: 99%